The Kneiphof-Library: International Library for the Kaliningrad State University and the City - Bloech, Jürgen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The overall objective of the Kneiphof-Library will contain easy access to a modern stock of literature of scientific subjects and international view, preservation of valuable books and information about the history of the region, the Wallenrodtsche Library and other scientific goals.